Media multitasking, attention, and distraction: a critical discussion. - Aagaard, Jesper (Phenomenology & the Cognitive Sciences, 2015)
Students often multitask with technologies such as computers, laptops, tablets and smartphones during class. Unfortunately, numerous empirical studies firmly establish a significant drop in academic performance caused by this media multitasking. In this paper it is argued that cognitive studies may have clarified the negative consequences of this activity, yet they struggle to address the processes involved in it. A cognitive characterization of attention as a mental phenomenon neglects the interaction between bodies and technologies, and it is suggested that a postphenomenological understanding is necessary to account for the materiality of practice. Notions of embodied habits and technical mediation are introduced, and an example of a postphenomenological account of media multitasking is introduced. It is argued that this approach enables researchers to investigate media multitasking as it occurs in everyday educational practice.